Clinico-hematological profile of paediatric patient admitted with acute leukemia in tertiary care centre of central India - Kumar, Saurabh; Anand, Shweta; Sahu, T P (Indian Journal of Child Health, 2016)
Background: Leukemia is the most prevalent childhood cancer. Acute lymphoblastic leukemia (ALL) constitutes 75% of all cases. Objective: To find out the most common clinical and hematological findings of pediatric patients with acute leukemia at a tertiary care center of central India. Materials and Methods: This retrospective study was done on 30 pediatric patients diagnosed with acute leukemia in the Department of Pediatrics and Oncology at Chirayu Medical College and Hospital, Bhopal. This study included children aged from 6 months to 15 years, who were admitted from June 2014 to June 2015. Data were retrospectivelycollected by reviewing medical records of these patients. Clinical history, physical examination, hematological, and radiological data were analyzed. Results: ALL was the most common hematological malignancy observed at our hospital. In addition, it was found to be more prevalent in males and fever was the most common presenting symptoms followed by fatigue and anorexia. Hepatosplenomegaly and pallor were the most common findings on clinical examination. Among patients with ALL, subtype L1 was the most common type. Among patients with acute myeloid leukemia, M2 and M3 subtypes were most commonly documented.